The use of reverse logistics for waste management in a Brazilian grocery retailer - Dias, Karina T.S. [UNESP]; Braga, Sergio Silva [UNESP] (SAGE Publications, 2016)
Retail growth is a result of the diversification of departments with the intention to look to consumer's needs and level of demand. Pressed by consumers and by the law, the adoption of environmental preservation practices is becoming stronger among grocery retailers. The objective of this research was to analyse the practices of reverse logistics performed by a retailer and measure the amount of waste generated by each department. To reach the proposed goal, a field research study was conducted to directly observe a grocery retailer in the state of Sao Paulo, Brazil, for a period of 6 months and monitor the amounts of cardboard and plastic discarded by each department. Using the Wuppertal method, the first result observed was that the retailer stopped its monthly production of approximately 20 tonne of biotic and abiotic material, which influence global warming and degradation of the ozone layer. Another result observed with the implementation of reverse logistics, was that the general grocery department mostly used cardboard and plastic. This sector includes products such as food cupboard, drinks, household, health and beauty, and pet articles. The fresh fruit and vegetable department and the meat, chicken and frozen department were increasingly using less plastic and cardboard packaging, increasing the use of returnable and durable packaging and thus promoting sustainability.
Keywords: Recycling; Retail; Reverse logistics; Solid waste; Sustainability; Waste management